2009 9th International Conference on Intelligent Transport Systems Telecommunications, (ITST) 2009
DOI: 10.1109/itst.2009.5399393
|View full text |Cite
|
Sign up to set email alerts
|

Scalability investigations on communication traffic in distributed routing of autonomous logistic objects

Abstract: Abstract-In current transport logistics, routing is usually done centrally. A dedicated routing instance solves the optimisation problem of finding the best solution to handle the current set of orders with the set of available vehicles under constraints such as vehicle utilisation, punctuality etc. Because of the increasing complexity of logistic processes, approaches have been suggested recently which change this centralised routing paradigm towards a distributed approach with autonomous logistic entities (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…To improve the scalability of information processing in large networks, various mechanisms to limit the propagation of transport requests can be added to the DLRP t . These include limitation of the search depth, intermediary assessment of partial routes for segments of the total route, re-using data from previous request propagations (Wenning et al 2009;Wenning 2010), or mechanisms for clustering and regional partitioning of transportation networks (Singh et al 2008).…”
Section: Transportation Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the scalability of information processing in large networks, various mechanisms to limit the propagation of transport requests can be added to the DLRP t . These include limitation of the search depth, intermediary assessment of partial routes for segments of the total route, re-using data from previous request propagations (Wenning et al 2009;Wenning 2010), or mechanisms for clustering and regional partitioning of transportation networks (Singh et al 2008).…”
Section: Transportation Schedulingmentioning
confidence: 99%
“…For the DLRP t , it could be shown that measures to improve the scalability of information processing can significantly reduce communication volumes in large networks without impairing the logistical achievement of objectives. For that reason, the DLRP t can be scaled to larger networks within the given limits of the communication infrastructure (Wenning et al 2009).…”
Section: Performance Of Autonomous Control and Influence Of Complexitymentioning
confidence: 99%
“…[5], [8]) has shown that the route discovery in DLRP can create a large amount of communication traffic if no measures are taken to limit this traffic. However, the main focus there has been on the overall network load, where the route requests are the main contribution.…”
Section: Communication Volumesmentioning
confidence: 99%
“…Previous work on the traffic volume in DLRP, as described in [5] and [8], utilized a scenario topology with 18 vertices based on a German road network. This scenario has now been extended to a topology with 40 vertices and a corresponding set of connections.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation